2010
DOI: 10.1248/cpb.58.312
|View full text |Cite
|
Sign up to set email alerts
|

Novel Preparation of Intercellular Lipid Models of the Stratum Corneum Containing Stereoactive Ceramide

Abstract: The stratum corneum, the outermost layer of the skin, plays the main barrier for the drug permeation via the skin. The barrier function of the stratum corneum is dominated by the microstructure formed by intercellular lipids in the stratum corneum consisting of ceramide (CER), cholesterol (CHOL), fatty acids, and their derivatives. The lipid microstructure, the molecular arrangement of intercellular lipids in the stratum corneum, has been investigated using synchrotron X-ray scattering and neutron diffraction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
0
8
0
6
Order By: Relevance
“…where q 15.08 is the integrated intensity of the diffraction peak at q = 15.08 nm −1 and q 16.78 is that of the peak at q = 16.78 nm −1 . The parameter q 16.78 corresponds to the signal of orthorhombic hydrocarbon chain packing.…”
Section: Methodsmentioning
confidence: 99%
“…where q 15.08 is the integrated intensity of the diffraction peak at q = 15.08 nm −1 and q 16.78 is that of the peak at q = 16.78 nm −1 . The parameter q 16.78 corresponds to the signal of orthorhombic hydrocarbon chain packing.…”
Section: Methodsmentioning
confidence: 99%
“…The former is derived from hexagonal and orthorhombic structures, and the latter is derived from only orthorhombic structures. 15,23,25) Figure 1 presents the synchrotron X-ray diffraction results for hairless mouse stratum corneum treated with water (W), 3.0% (w/w) levulinic acid (L3), 1.0% (w/w) nerolidol +3.0% (w/w) levulinic acid (N1L3), and 1.0% (w/w) nerolidol (N1) at 20°C. The profile of L3 was nearly identical to that of W. By contrast, the stratum corneum treated with nerolidol (N1, N1L3) exhibited a significant decrease in intensity, and gel lipids occurred near 2.2 nm…”
Section: Effect Of Permeation Enhancers On Synchrotron X-ray Diffractmentioning
confidence: 99%
“…In light of the disappearance of lateral packing at 60 after 1 h, as shown by SAXS, it is possible that packed lipids are annealing when the model lipids are exposed to a certain higher temperature for a certain period of time. H. Watanabe et al demonstrated that the phase diagram of Cer 5 2-hydroxyacyl sphingosine /Chol/PA i.e., Cer 5/ Chol/PA bilayer was classifi ed into 4 clusters, with no distinct phase transition temperature observed in cluster 3, as measured by fluorescence anisotropy 20 . The liposomes used in our present studies, consisting of Cer 2 non-hydroxyacyl sphingosine /Chol/PA at 12.5/34.5/53, correspond to cluster 3 in their phase diagram.…”
Section: Physicochemical Analysesmentioning
confidence: 99%